Using an innovative educational song in training on three-part compositions through singing and dictation in the subject of auditory training (Comprehensive Journal of Science, 2026)
The research aims to identify innovative educational songs in training on types of triadic harmonics, singing and dictation, to benefit from them in teaching the subject of auditory training. The descriptive method (content analysis) was used, and a sample of musical exercises was used. Among the most important results reached by the researcher is the benefit of melodies and songs in some of the Rast maqam and teaching methods for the subject of auditory training (reading and notation) and Arabic singing (memorization and listening).